Global value chains and production networks : case studies of Siemens and Huawei - Cui, Fengru; Liu, Guitang (Academic Press, and imprint of Elsevier, 2019)
"Global Value Chains and Production Networks: Case Studies of Siemens and Huawei presents theories and frameworks that facilitate the evolution of GPN studies, from macro perspectives based on territory and industry to the use of micro (firm-level) data. The book explores these theories and frameworks through detailed case studies of two major corporations, Siemens and Huawei. With the GPN/GVC structure of Chinese firms not well known outside China, despite the growing importance of Chinese firms in the global economy, this guide plays a pivotal role in facilitating the use of data that promise to unlock economic cooperation and value."--Provided by publisher